Satellite Observations of the Impact of Individual Aircraft on Ice Crystal Number in Thin Cirrus Clouds. Issue 5 (24th February 2022) - Marjani, Sajedeh; Tesche, Matthias; Bräuer, Peter; Sourdeval, Odran; Quaas, Johannes
Abstract: Contrails can persist in cloud‐free supersaturated air, increasing high‐cloud cover, and inside natural cirrus cloud, modifying the microphysical properties of them. The latter effect is almost unknown, partly because of the lack of height‐resolved measurements and the capability of measurements to penetrate inside the cloud. New retrievals of the ice crystal number concentration from combined satellite cloud radar and lidar measurements (CloudSat/CALIPSO; DARDAR‐Nice algorithm) now allow for satellite‐based assessment inside the clouds. We investigate this issue at intersections between the aircraft flight tracks and these retrieval profiles. Regions behind the aircraft inside the flight track were compared to the adjacent regions and to ahead of the aircraft, along the satellites' profiles, where DARDAR‐Nice identify geometrically thin cirrus clouds. This comparison revealed a statistically significant increase of 25% and 54% in the concentration of ice crystals with the minimum size of 5 μm around 300–540‐m beneath an aircraft's flight altitude. Plain Language Summary: Aircraft emissions are the only human‐made source of pollution that is directly injected into the upper troposphere. Aircraft can form trails of ice crystals in a cloud‐free atmosphere and therefore change the high‐cloud cover. If they form inside the already existing cirrus clouds, they will modify the cloud microphysical properties, an effect that is not well quantified so far. In this study, we use a new retrieval of ice crystal number concentration from satellite lidar and radar, which provides height resolved information. We analyze intersections between the aircraft flight tracks and the swath of the satellite by comparing the ice crystal concentration in the regions affected by aviation with the neighboring regions and those ahead of the aircraft. The result of this work reveals a statistically significant increase in ice crystal concentration within clouds a few hundred meters beneath the flight height. Key Points: New satellite retrievals of ice crystal number concentration allow to assess microphysical effects of aviation on existing cirrus clouds Comparison of ICNC profiles on existing cirrus clouds shows increase after aircraft by 25% and 54% ICNC The signal is the largest 300–540 m below the flight altitude